1954
DOI: 10.1021/ja01635a050
|View full text |Cite
|
Sign up to set email alerts
|

Autocatalysis in Aromatic Alkylations. The Reaction of Phenols with Triphenylmethyl Chloride1

Abstract: resulting mixture was refluxed for 13 minutes with stirring. After dilution with water, separation and drying over anhydrous magnesium sulfate, the product was distilled at 75-76' at 1 mm. (rep0rted~980.5" a t 0.8 mm.) yielding 25.1 g. (72%) of colorless p-bromostyrene oxide, m.p. 27.1' (re-ported18 26').p-Bromostyrene oxide (26.9 g.) reduced with 3.0 g. (4!0%) of lithium borohydride, gave an 83% yield of a mixture containing 20.4 g. (91%) of a fraction distilling a t 86-92" a t 1 mm. [largely l-(4-bromophenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1955
1955
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Hart and Cassis, who studied this reaction and the corresponding reaction of o-cresol with trityl chloride, yielding p-trityl-o-cresol, concluded that the most likely role of HCl is in facilitating the ionization of trityl chloride, as represented by the following equation [505]:…”
Section: Homoconjugate Phenolate Ionsmentioning
confidence: 99%
“…Hart and Cassis, who studied this reaction and the corresponding reaction of o-cresol with trityl chloride, yielding p-trityl-o-cresol, concluded that the most likely role of HCl is in facilitating the ionization of trityl chloride, as represented by the following equation [505]:…”
Section: Homoconjugate Phenolate Ionsmentioning
confidence: 99%
“…The reaction of phenol with triphenylmethyl chloride in an inert solvent yields the p-alkylated phenol and can be catalyzed by hydrogen chloride (309). Alkylation of phenols by a-phenylethyl chloride may be similarly accomplished to give ortho or para substitution or a mixture depending on the structure of the phenol used.…”
Section: A Alkylation Of Aromatic Systemsmentioning
confidence: 99%
“…Although the rate of solvolysis of alkyl chlorides is usually not affected by the addition of acid (7,8) exceptions have been noted in the case of chloroethers (9, 10) and the reaction of trityl chloride with phenol (11). With respect to alkyl fluorides, however, several workers (3,6,(12)(13)(14) have discovered enhanced rates in the presence of acid.…”
Section: Discussionmentioning
confidence: 99%